PENGALAMAN IBU PEDAGANG DALAM MERAWAT ANAK - Nur Azizah; Elis Hartati (Jurusan Keperawatan, Universitas Diponegoro, 2012)
Child care is a mother duty as a homemaker. This duty is shifted because of the increasing number of working mother. The interviews data explained that the number of trader’s mother at Adiwerna Market Tegal Regency were 405 (73,24%) from 553 traders. Mother’s job as a trader has impact on the experiences in caring for children. The purpose of this research was to identify the experiences of trader’s mother in childcare at Adiwerna market Tegal regency. This research was using phenomenological qualitative design with Collaizi data analyze. The data were collected from 4 participants through in depth interview. The result of this research was showed 14 themes, such as: to do the mother’s role in household duties; to do the activities as a mother; to fulfill of children needs; the goals of childcare for child and mother; the action to fulfill the children need; the positive and negative impacts of trade in childcare; the internals and externals helps of the mother to care the children; the internals and externals fences of the mother to care the children; the existence of child care and market service unit. The result of this study is expected to provide recommendation of input for community nurses to be more active to improve the childhealth in the market community